A Midgut Digestive Phospholipase A2 in Larval Mosquitoes, Aedes albopictus and Culex quinquefasciatus. (15th May 2018) - Abdul Rahim, Nor Aliza; Othman, Marlini; Sabri, Muna; Stanley, David W.
Abstract : Phospholipase A2 (PLA2 ) is a secretory digestive enzyme that hydrolyzes ester bond at sn-2 position of dietary phospholipids, creating free fatty acid and lysophospholipid. The free fatty acids (arachidonic acid) are absorbed into midgut cells. Aedes albopictus and Culex quinquefasciatus digestive PLA2 was characterized using a microplate PLA2 assay. The enzyme showed substantial activities at 6 and 8  μ g/ μ l of protein concentration with optimal activity at 20 and 25  μ g/ μ l of substrate concentration in Aedes albopictus and Culex quinquefasciatus, respectively. PLA2 activity from both mosquitoes increased in a linear function up to 1 hour of the reaction time. Both enzymes were sensitive to pH and temperature. PLA2 showed higher enzyme activities in pH 8.0 and pH 9.0 from Aedes albopictus and Culex quinquefasciatus, respectively, at 40°C of incubation. The PLA2 activity decreased in the presence of 5 mM (Aedes albopictus) and 0.5 mM (Culex quinquefasciatus) site specific PLA2 inhibitor, oleyloxyethylphosphorylcholine. Based on the migration pattern of the partially purified PLA2 on SDS-PAGE, the protein mass of PLA2 is approximately 20–25 kDa for both mosquitoes. The information on PLA2 properties derived from this study may facilitate in devising mosquitoes control strategies especially in the development of inhibitors targeting the enzyme active site.